Prototype of Manipulative Basic Movement Learning Model Based on Augmented Reality - Rahma Dewi; Indah Verawati; Bessy Sitorus Pane; Muhammad Reza Destya (Journal of Education Reseach and Evaluation, 2024)
In the increasingly advanced digital era, technology has penetrated various aspects of life, including the field of education. One technological innovation that has great potential to improve the quality of learning is Augmented Reality (AR). AR enables the combination of the real world with digital elements, providing a more interactive and immersive learning experience. In the context of physical education, especially in learning basic manipulative movements, the application of AR can be a solution to overcome various obstacles faced so far, such as limited facilities, difficulties in visualizing movements, and lack of practical interaction. This research aims to develop a model for learning basic manipulative movements based on augmented reality and develop it into a guide for students and sports teachers in teaching basic movements. The resulting product is a basic manipulative learning model based on augmented reality, a guidebook for application use. This research was developed by adapting the Borg & Gall model of educational research and development. The development procedures used include the stages of analyzing the content of the product being developed, developing the initial game product, expert validation, field trials, product revision. The data analysis technique used in this research is in two ways, namely quantitative and qualitative. The results of the research show that the augmented reality-based basic manipulative movement learning model can assess elementary school students' abilities, the application developed by researchers is also easy to use by PJOK teachers in assessing the augmented reality-based basic manipulative movement learning model which can be carried anywhere by PJOK teachers. portable. Implications This research can provide guidance for educational software developers to create AR applications that are more relevant and useful in learning contexts.